IMAGING FINDINGS IN GALL BLADDER CARCINOMA IN NORTHEASTERN THAILAND - CHAMADOL, Nittaya; ANUKULANANCHAI, Thitima (The ASEAN Journal of Radiology, 2023)
Early detection of gallbladder carcinoma is difficult. The objective of this study was to review the imaging findings that could be found in carcinoma of the gallbladder, as an attempt to identify more details, which might be helpful for future sooner diagnosis of this disease. All imaging studies including US, CT and MRI of 21 patients with pathological proven carcinoma of gall bladder in 6-year-period. The patients were 15 women and 6 men, mean age 64 years. Abdominal pain was the most frequent presentation. Polypoid mass within gall bladder lumen was the most common finding; 83.3 % US, 75 %CT, followed by gallstones (41.6 %-US), focal wall thickening (33 %-US), lymphadenopathy (33 %-CT), liver invasion (25 %- CT), IHD dilatation (25 %-CT), and mass obscured gall bladder (8.3 %-US, 25%-CT). CT is superior to US in identifying the extension of disease and tumor staging. But US is preferred as the first line of investigation. Various manifestations of gall bladder carcinoma will be presented. If the disease recognized and managed properly, the patient’s life MAY - AUG. 2003 Volume IX Number II expectancy will be improved.